Species composition, structure and biomass of zooplankton in the Chukchi Sea in August-September 2019 - N. A. Kuznetsova; K. M. Gorbatenko; A. L. Figurkin (Известия ТИНРО)
Plankton survey was conducted in the Chukchi Sea in August-September 2019 by two research vessels: RV Professor Levanidov in the western part of the sea and RV Ocean Starr in its eastern part. Parasagitta elegans dominated everywhere in zooplankton. Beside these arrowworms, species of the arctic and arctic-boreal complex were abundant in the northwestern Chukchi Sea, as Calanus glacialis and other species typical for the adjacent East-Siberian Sea. C. glacialis was numerous in the northeastern Chukchi Sea, too, together with species of the Arctic waters and the Beaufort Sea. The southern Chukchi Sea was occupied by the waters invaded from the Bering Sea, so species of the Bering Sea complex were abundant there, as Eucalanus bungii and Neocalanus plumchrus/flemingeri, at Alaska coast together with neritic species typical for the Alaska coastal water mass. The zooplankton community structure corresponded to the spring phase of seasonal succession in the northern area, whereas to the summer phase in the southern area. Total density of zooplankton was estimated as 65 t/km2 for the northwestern part of the sea, presented mostly by large-sized fraction (56 t/km2) including arrowworms (35 t/km2) and copepods (13 t/km2), and as 48 t/km2 for the southwestern part of the sea, also mostly large-sized fraction (40 t/km2). So high zooplankton density in the western Chukchi Sea is considered as result of the Bering Sea waters advection (previously such abundance was observed in 2008 — 40 and 36 t/km2, when the advection was also active). In the eastern Chukchi Sea, the total density of zooplankton was 44 t/km2 in the northeastern area (including 29 t/km2 of large-sized fraction) and 43 t/km2 in the southeastern area, that was higher than in 2017 (15 t/km2) but lower than in 2007 (49 t/km2). However, different phases of seasonal succession should be noted: summer season in 2019, spring season in 2017, and late-summer season in 2007.